Envisages of new product developments in small and medium enterprises through virtual team - Ale Ebrahim, N.; Ahmed, S.; Taha , Z. (2010)
New product development (NPD) in small and medium-sized enterprises (SMEs) virtual team has not been systematically investigated in developing countries. Literatures have shown no significant differences between traditional NPD and virtual NPD in general. New product development especially for SMEs virtual team are somewhat lacking in the literature and constitute a research gap. This paper aims to bridge this gap. This study first reviews the NPD and its relationship with virtuality and then identifies the critical factors in definition of NPD in SMEs virtual team. The statistical method was utilized to perform the required analysis of the data from survey. The results are achieved through factor analysis at the perspective of NPD in some of Malaysian and Iranian manufacturing firms. The 20 new product development factors were grouped into five higher level constructs. It gives valuable insight and guidelines which hopefully will help managers of firms in developing countries to consider the main factors in NPD.